Bad boys of fashion : style rebels and renegades through the ages - Croll, Jennifer, 1980- (Annick Press, 2019)
Profiles many men throughout history to the present and discusses their fashion styles, highlighting how they have used clothing to define their personalities, make statements, and establish their power and legacies--from Louix XIV of France up to Kanye West.